2022
DOI: 10.1080/13880209.2022.2143534
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the oral absorption and systemic disposition of zeaxanthin in rats: in vitro , in situ , and in vivo evaluations

Abstract: Context Zeaxanthin is a yellow‑coloured dietary carotenoid widely recognized as an essential component of the macula. It exerts blue light filtering and antioxidant activities, offering eye health and vision benefits. Objective This study explores the oral absorption and systemic disposition of zeaxanthin from biopharmaceutical and pharmacokinetic perspectives. Materials and methods In vivo intravenous (5 and 10 mg/kg) and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Several factors might have contributed to these findings. One of the causes may be low bioavailability due to chemical degradation of phytochemicals and the intestinal/hepatic first pass [ 38 , 41 , 49 , 50 ], and plasma and liver concentrations of inhibitors may be insufficient for the IC 50 obtained in vitro CYP inhibition studies [ 51 , 52 ]. Consequently, a single oral dose of WGM did not have significant effects on the pharmacokinetics of buspirone in rats, suggesting that WGM cannot function as an inhibitor of CYP3A-mediated metabolism in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors might have contributed to these findings. One of the causes may be low bioavailability due to chemical degradation of phytochemicals and the intestinal/hepatic first pass [ 38 , 41 , 49 , 50 ], and plasma and liver concentrations of inhibitors may be insufficient for the IC 50 obtained in vitro CYP inhibition studies [ 51 , 52 ]. Consequently, a single oral dose of WGM did not have significant effects on the pharmacokinetics of buspirone in rats, suggesting that WGM cannot function as an inhibitor of CYP3A-mediated metabolism in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effects of WGM on the pharmacokinetics of BUS in vivo, 12 rats underwent surgical cannulation of the femoral artery after anesthetization via an intramuscular injection of 10 mg/kg zoletil [ 40 , 41 ]. After sufficient recovery from anesthesia, 6 rats were administered a single oral dose of BUS (30 mg/kg) and 6 rats were administered WGM (1 g/kg) together with BUS.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of visual fatigue is related to ocular muscle fatigue, eye dryness, retinal dysfunction, and other factors. Recent studies have shown that oxidative stress is also closely related to the occurrence of visual fatigue [25,26].…”
Section: Discussionmentioning
confidence: 99%